The implementation of e-learning with team builder at vocational high schools - Patwary, Mahmud Al Haq; Surjono, Herman Dwi (REID (Research and Evaluation in Education), 2015)
This research is aimed at: (1) producing an appropriate e-learning for English language studies in vocational high school, (2) evaluating the suitability of the developed e-learning in terms of appropriateness, accuracy and clarity, screen presentation and design, and appropriateness of the team builder module aspect, and (3) evaluating the effectiveness of the e-learning in practical application. This research and development (R&D) study used Alessi and Trollip's model rearranged following ADDIE model, where the development of instruction followed Dick and Carey's model and the need assessment procedures were adapted from Lee & Owens. Overall appropriateness and quality of the e-learning from alpha testing is "˜very appropriate' and from beta testing is "˜excellent'. Alpha testing reveals that, the Team Builder Module is "˜very appropriate' and beta testing reveals that, its overall quality is "˜excellent'. The e-learning is highly effective. The average score of the students raises 3.82 points (or 42.44%) in the post-test from pre-test score. The minimum score of the post-test (i.e. 8) is more than the maximum score of the pre-test (i.e. 7), so it is concluded that the use of e-learning does not deteriorate the performance of the students, but improves their performance.